ELECTRONIC DICTIONARIES AS A MODERN PRODUCT LEXICOGRAPHY - Kambarova Liliya.Ruslanovna; Duvlaeva Nozigul Xolmuxammat qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The article discusses the positive and negative features of electronic (computer) dictionaries. Considering the relevance of this problem, the purpose of the article is to determine the didactic possibilities of using electronic dictionaries to develop the speech activity of students of non-linguistic specialties while studying a foreign language. In order to give readers a thorough grasp of electronic dictionaries as a significant output of contemporary lexicography, this paper uses a mixed-methods approach that includes a systematic literature review, comparative analysis, and user surveys.